Multivesicular Liposomes for Glucose-Responsive Insulin Delivery - Guangqu Liu; Suping He; Yu Ding; Cai Chen; Qingchun Cai; Wei Zhou (MDPI AG, 2021)
An intelligent insulin delivery system is highly desirable for diabetes management. Herein, we developed a novel glucose-responsive multivesicular liposome (MVL) for self-regulated insulin delivery using the double emulsion method. Glucose-responsive MVLs could effectively regulate insulin release in response to fluctuating glucose concentrations in vitro. Notably, in situ released glucose oxidase catalyzed glucose enrichment on the MVL surface, based on the combination of (3-fluoro-4-((octyloxy)carbonyl)phenyl)boronic acid and glucose. The outer MVL membrane was destroyed when triggered by the local acidic and H2O2-enriched microenvironment induced by glucose oxidase catalysis in situ, followed by the further release of entrapped insulin. Moreover, the Alizarin red probe and molecular docking were used to clarify the glucose-responsive mechanism of MVLs. Utilizing chemically induced type 1 diabetic rats, we demonstrated that the glucose-responsive MVLs could effectively regulate blood glucose levels within a normal range. Our findings suggest that glucose-responsive MVLs with good biocompatibility may have promising applications in diabetes treatment.